Analisis Financial Literacy dan Financial Inclusion Terhadap Business Sustainability Melalui Financial Behavior Sebagai Variabel Mediasi Pada Pelaku UMKM Minuman Di Kota Sukabumi - Siti Rohila; Nor Norisanti; R. Deni M. Danial (Journal of Economic, Bussines and Accounting (COSTING), 2024)
In the Indonesian economy, Micro, Small and Medium Enterprises (MSMEs) play an important role in developing economic activities. Financial problems are one of the problems that often occur in micro, small and medium scale businesses (MSMEs) in Indonesia. This research aims to determine the influence of Financial Literacy and Financial Inclusion on Business Sustainability which is mediated by Financial Behavior. The population in this study were beverage MSMEs in Sukabumi City. There were 140 MSMEs sampled in this research, which was the result of a probability sampling technique using simple random sampling. The analysis technique used in this research is path analysis . The results of this research show that (1) Financial Literacy does not have a significant influence on Business Sustainability (2) Financial Inclusion has a significant influence on Business Sustainability , (3) Financial Behavior has a significant influence on Business Sustainability , (4) Financial Behavior cannot mediate the relationship between Financial Literacy and Business Sustainability , and (5) Financial Behavior mediates the relationship between Financial Inclusion and Business Sustainability.